Exploration Of Prospective Mathematics Teachers' Knowledge Of The History Of The Development Of Hindu (Indian) Mathematics - Harisman, Yulyanti; Shandi, Dhiya Harisa Tri; Hafizatunnisa, Hafizatunnisa (JNPM (Jurnal Nasional Pendidikan Matematika), 2024)
This Hindu mathematics is one of the most significant contributions of Indian civilization to the development of world science. The Hindu numeration system is the most prominent contribution in the history of mathematics The purpose of this study was to determine the extent of the understanding of prospective Mathematics teachers regarding the mathematical history of the development of Hindu (Indian) Mathematics. The population of this study is Mathematics Education students of 2021, 2022 and 2023 who have taken history of mathematics courses. Through explorative analysis, this study shows their level of understanding of the History and numeration system of Hindu mathematics. This research adopts a qualitative research type with literature review and case study methods, while the instrument used is an open-ended interview to evaluate students' understanding. The data analysis in this study is thematic analysis. The results show varying levels of understanding, with some students having in-depth knowledge of the development of Hindu (Indian) mathematics, while others need improved understanding. The implication of this result is the need for a more in-depth and focused learning approach on the historical aspects of Hindu mathematics.